All for one or all for three: Empirical evidence of paradox theory in the triple-bottom-line. (1st December 2020) - Walker, Kent; Yu, Xin; Zhang, Zhou
Abstract: We empirically examine the triple-bottom-line of a sample of 746 firms from 2003 to 2013. The business case for sustainability advocates for corporate responsibilities only if they strengthen profits. In contrast, paradox theory states that managers should embrace the tensions between multiple bottom lines seeking simultaneous benefits. Combining data from KLD and Compustat, we find strong supporting evidence for paradox theory. First, the findings suggest that the three components of the triple bottom line move in tandem, rather than being mutually exclusive, where high (poor) performance in one dimension relates to high (poor) performance in the other two dimensions, regardless of the economic conditions. Second, using the Great Recession as an exogenous shock, we find supporting evidence for paradox theory. Lastly, we link paradox theory and its implication on market valuation; we find that the more components achieved at a high level, the higher the market valuation, with the valuation increasing per component achieved. We conclude that the traditional focus on scarcity and the mutual exclusivity of sustainability goals is not empirically supported in our study. Instead, we find compelling evidence for the abundance perspective of paradox theory and the simultaneous achievement of sustainability goals. Our results highlight that in viewing three bottom lines, managers should embrace any ostensible tensions to find creative ways to address all three instead of all for one.